Strategi Pengembangan Model Rujukan dengan Menggunakan Sisrute di Puskesmas Pangkoh - Tara, Elena Silvia; Purwadhi, Purwadhi; Hidayat, Dasrun (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
This study aims to develop a referral model strategy to enhance the effectiveness of the referral system at Pangkoh Community Health Center (Puskesmas) using the SISRUTE application. The research employs a qualitative approach through in-depth interviews and observations with 10 key informants, including various professionals at the Puskesmas and the Health Department. The analysis focuses on the stages of SISRUTE usage, human resource (HR) competency, infrastructure and technology, monitoring and evaluation, referral system effectiveness, and government policies and support. The findings indicate that the implementation of SISRUTE has improved the efficiency of the referral process, though challenges related to infrastructure limitations and HR competency remain. Future development of the referral system emphasizes enhancing HR training, strengthening technological infrastructure, and ensuring sustainable policy support. This strategy is expected to improve the quality of healthcare services, increase accessibility, and expedite the referral process, thereby supporting the achievement of public health goals in the Pangkoh Puskesmas service area.